A rare case of single coronary artery with congenital absence of right coronary artery - Rajbhandari, Rajib; Shah, Jageshwar Prasad; Pradhan, Arya; Dangol, Rebika; Dangol, Utsav (Journal of Advances in Internal Medicine, 2023)
A single coronary artery (SCA) is a relatively rare coronary artery anomaly. Absent right coronary artery (RCA) is the rarest of coronary artery anomalies occurring when the right coronary artery doesn’t develop. In the past 14 years till 2020, only 26 cases of congenital absence of RCA have been reported in 24 articles. We report a rare case of single left coronary artery with congenital absence of right coronary artery detected by coronary angiography and confirmed by coronary CT angiography. The RCA territory was being supplied by a branch from left circumflex (LCX) artery. The patient presented with nonspecific central chest pain. We aim to shed light on this rare anomaly and raise awareness among medical practitioners.